CAPITAL STRUCTURE AND FIRM VALUE NEXUS: THE MODERATING ROLE OF AGENCY COST - Destriana, Nicken; Zilfikar, Rudi; Mulyasari, Windu; Ismawati, Iis (Journal of Applied Finance and Accounting, 2025)
This study aims to examine the linear and non-linear relationship between capital structure (CS) and firm value (FV) and examine the moderating role of agency costs in the CS-FV relationship. The study employs static and quadratic regression analysis on panel data consisting of 318 observations from non-financial firms to examine the linear and non-linear relationships between capital structure and firm value. The data is sourced from non-financial companies listed on the Indonesia Stock Exchange over the period of 2021-2023. Capital structure has a significant positive effect on firm value. Agency costs are significantly and negatively associated with firm value. There is a strong non-linear relationship between capital structure and firm value that supports trade-off theory and agency costs. Agency costs are an important moderator in the CS-FV relationship. Overall, the sensitivity analysis shows that the results are robust. Firms need to carefully consider the level and type of debt and equity in their CS to deal with changing economic conditions.  The moderating effect of agency costs can assist firms in optimizing capital structure, emphasizing the importance of aligning interests to encourage sustainable business practices. This study enhances the existing literature by presenting new evidence concerning the non-linear relationship between capital structure and firm performance, as well as the moderating role of agency costs in this relationship, specifically within emerging capital markets, where research in this area remains limited.